1995
DOI: 10.1172/jci117988
|View full text |Cite
|
Sign up to set email alerts
|

Mast cells and histamine contribute to bile acid-stimulated secretion in the mouse colon.

Abstract: Certain dihydroxy bile acids cause secretory diarrhea when present in the colonic lumen at inappropriately high concentrations. However, the mechanism underlying the secretagogue activity has not been fully elucidated. Experiments were performed to test whether mast cells and one of their major mediators, histamine, might contribute to the secretory effect. Chenodeoxycholic acid, a secretory bile acid, and ursodeoxycholic acid, a nonsecretory, hydrophilic bile acid, were compared for their ability to induce ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
64
1

Year Published

1995
1995
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(68 citation statements)
references
References 33 publications
3
64
1
Order By: Relevance
“…In these experiments, CA inhibited PMC amplitude after addition of 5-HT3 antagonist, 5-HT4 antagonist and H1 anta-gonist. These results were in agreement with previous studies which demonstrated that BAs are able to activate mast cells (Gelbmann et al, 1995;Fihn et al, 2003) and act via 5-HT3 receptor. Therefore, the inhibition of CA in the presence of histamine antagonist on PMCs suggested that mast cells are playing an important role in mediating hyperexcitability and enteric neuron depolari-zation via their release of histamine from mast cell degranulation (Sand et al, 2009).…”
Section: Discussionsupporting
confidence: 94%
“…In these experiments, CA inhibited PMC amplitude after addition of 5-HT3 antagonist, 5-HT4 antagonist and H1 anta-gonist. These results were in agreement with previous studies which demonstrated that BAs are able to activate mast cells (Gelbmann et al, 1995;Fihn et al, 2003) and act via 5-HT3 receptor. Therefore, the inhibition of CA in the presence of histamine antagonist on PMCs suggested that mast cells are playing an important role in mediating hyperexcitability and enteric neuron depolari-zation via their release of histamine from mast cell degranulation (Sand et al, 2009).…”
Section: Discussionsupporting
confidence: 94%
“…It is well known that BAs elicit fluid secretion and also increased permeability in the gastrointestinal tract [97][98][99][100][101] . BAs also affect intestinal motility, although this field of study has received relatively little attention [1,102] .…”
Section: Effect Of Ba On Ion Transportmentioning
confidence: 99%
“…This effect is to a large extent indirect, induced by intramural reflexes containing nicotinic receptors, but probably it does not involve histamine or nitric oxide pathways [97,103,104] . However, this question is controversial, because in some cases histamine has been suggested to be involved [98] . The secretory effect of BAs has been studied in the small and large intestine, and in both cases the mechanism of secretion appears to be largely indirect [99] .…”
Section: Effect Of Ba On Ion Transportmentioning
confidence: 99%
See 2 more Smart Citations